In vitro effectiveness of the filtration in three and four layered surgical masks after a few hours exposure of S. aureus: experiment study - Putri, Aliati; Yasrin, Tadeus Arufan; Pramesti, Hening Tjaturina; Arief, Erry Mochamad (Padjadjaran Journal of Dentistry, 2023)
ABSTRACTIntroduction: Surgical masks commonly have many layers. The outer layer acts as the initial filtration and the protection for the middle layer, the middle layer acts as the primary filtration, and the innermost layer absorbs liquid to prevent the spread of droplets from the mask's wearer. The recommended duration of wearing medical and fabric masks is 4–6 hours, while some studies stated that the maximum duration is 8 hours. The use of S. aureus in this study was based on its clinical relevance as a major cause of nosocomial infections. This study aimed to analyze the effectiveness of the filtration in three-layer and four-layer masks against S. aureus. Methods: This experimental study followed the methods of previous research, and followed the Standard Test Method from SNI 8489 2018 with several adjustments consisting of several steps, i.e., preparation of tested masks, bacterial culture media, and tested bacteria; determination of masks’ filtration efficacy; confirmation of the efficacy. All steps were repeated 15 times with exposure times of 2, 4, 6, and 8 hours and analysis using the chi-square test. Results: The percentage of surgical masks filtration effectiveness was indicated by the growth of S. aureus in Nutrient Agar media. The four-layer surgical masks showed the highest percentage (80%) of 2 hours and 4 hours of usage. Both types showed the lowest percentage of 8 hours of usage. Based on the duration of wearing, the mask's filtration effectiveness from the highest and lowest score was the S. aureus-exposed media for 2, 4, 6, and 8 hours, respectively p<0.050. The comparison value for the effectiveness of mask filtration between the type of masks and the length of use was 0.003. Conclusion: The filtration effectiveness of the four-layer masks is higher than the three-layer masks according to the duration of wearing the masks.Keyword : Surgical masks, filtration, duration, S.aureus